1975
DOI: 10.1007/bf01073132
|View full text |Cite
|
Sign up to set email alerts
|

Control factors in the release of gastrin by direct electrical stimulation of the vagus

Abstract: The release of gastrin by direct electrical stimulation of the vagus was studied together with the relative effects on the response of antral and duodenal acidification. As expected, gastrin levels increased to three times the normal simulated response following antral neutralization. In contrast, duodenal acidification failed to influence the vagal release of gastrin when the antrum was neutralized although it had a minor effect when the antrum was acidified. Thus the antral pH dominates over duodenal pH as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 26 publications
3
3
0
1
Order By: Relevance
“…units nerve fibres within the vagus are probably not responsible for the release of 5-HT from the EC. A similar, presumably non-cholinergic (atropine-resistant) mechanism has previously been demonstrated for the vagal release of gastrin in dogs (Smith et a/. 1975).…”
Section: Discussionsupporting
confidence: 71%
“…units nerve fibres within the vagus are probably not responsible for the release of 5-HT from the EC. A similar, presumably non-cholinergic (atropine-resistant) mechanism has previously been demonstrated for the vagal release of gastrin in dogs (Smith et a/. 1975).…”
Section: Discussionsupporting
confidence: 71%
“…Gastrin is found in the granules of G-cells which are principally located in the gastric antrum and is released by vagal stimulation [3][4][5], Our study also showed that both pe ripheral and portal gastrin levels were in creased following electrical vagal stimulation in the control group. But in the gastrectomy group, there were no responses and the levels were significantly decreased due to the loss of G-cells.…”
Section: Discussionsupporting
confidence: 64%
“…These cholinergic influences are controlled to some degree by long vago-vagal reflexes (Harper, Kidd & Scratcherd, 1959;Grossman, 1962;Debas, Konturek, Walsh & Grossman, 1974;Debas, Walsh & Grossman, 1975), and by local cholinergic reflexes which have been identified in the absence of vagal innervation (Grossman, 1961;Magee & Hu, 1975). A possible role for a local cholinergic mechanism in the control of acid secretion has been studied using atropine in animals in which the vagal innervation to the whole stomach or a fundic pouch has been severed, although it must be appreciated that atropine may also influence acid secretion by inhibiting gastrin release from the pyloric antrum; an effect which remains to be firmly established (Smith, Kewenter, Connell, Ardill, Hayes & Buchanan, 1975). In addition, gastrin has been shown to release acetylcholine from the myenteric plexus in guinea-pig ileum (Vizi, Bertaccini, Impicciatore & Knoll, 1972, 1973 and it is possible that the secretagogue action of gastrin on the stomach is partly mediated through the release of acetylcholine.…”
Section: Introductionmentioning
confidence: 99%